A qualitative study on malaysian academics' perceptions and a qualitative study on malaysian academics' perceptions and suggestions on gamified learning - Eltahir, Mohd Elmagzoub; Annamalai, Nagaletchimee; Arulselvi, Uthayakumaran; Zyoud, Samer H.; Zakarneh, Bilal Ibrahim; Alsalhi, Najeh Rajeh (Peace and Conflict Studies, 2023)
This study explores lecturers' perceptions and suggestions on integrating gamified lessons in Malaysian higher institutions. The COVID-19 pandemic has drastically changed the norm of traditional classroom teaching by accelerating digital integration amongst educators and necessitating the need to address classroom gamification. To further understand educators' perceptions, we conducted in-depth interviews with 25 lecturers. We thematically analyzed the interviews by following the steps undertaken by Braun and Clarke (2006) to identify the emerging themes. The findings determine that educators found gamification suitable in teaching and learning activities during the set induction, reinforcement and assessment of specific skills. Several misconceptions also evident in this study. We conclude that although educators are familiar with gamification, they have not fully utilized the strength of gamification.